FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PROGRAM PENGEMBANGAN BUDAYA KERJA DI SEKRETARIAT DAERAH KABUPATEN PATI - Arif Arianto; Soesilo Zauhar; Imam Hanafi (Universitas Tribhuwana Tunggadewi, 2015)
Culture set development programs should be able to improve the performance and productivity of employees, but the empirical evidence shows no significant change due to the program implementation.The fact shows there is an implementation gap in the implementation of culture set development programs in the Regional Secretariat of Pati regency. Therefore, it is necessary to search for the factors that affect the implementation of the program which includes: communication, resources, attitudes, bureaucratic structure, program content and environmental.The objectives of this research is to test the influence of communication, resources, attitudes, bureaucratic structure, program content and environmental simultaneously and partially on the implementation of the cultural set development programs in the Regional Secretariat of Pati regency. The research method used in this research is quantitative method with the type of explanation. Respondents include civil servants in the Regional Secretariat of Pati Regency, where sampling using the formula Roscoe with proportionate stratified random sampling technique. The analytical techniques used in this research is the multivariate analysis with statistical techniques of Multiple Linear Regression. Based on these results it can be concluded that the factor of communication, resources, attitudes, bureaucratic structures, program content and environment has a significant influence either simultaneously or partially to the implementation of the culture set development programs in the Regional Secretariat of Pati regency. Where the communication variable are variables that most influence than other variables.